Gigantic Cutaneous Horn: a Clinical Case and a Literature Review - Suslavičius, Kristupas; Mačys, Žygimantas; Rauba, Gediminas (Lietuvos chirurgija, 2022)
Keratoacanthoma is a benign skin tumour caused mainly by ultraviolet A radiation. It affects 150 out of every 100 000 people worldwide. The most common location is the face, neck, and hands. Keratoacanthoma usually affects middle-aged and older men with a fair skin phenotype. More importantly, this disease may be a complication of cutaneous cornification. Keratoacanthoma is described as a circumscribed conical prominent hyperkeratotic lesion in the literature, and the main factor provoking this complication is ultraviolet radiation. Fair skin phenotype, male sex, and older age may contribute to the development of cutaneous horn disease. Another possible complication of keratoacanthoma is squamous cell carcinoma, which is defined as a malignant composed of epidermal keratinocytes skin tumour. Squamous cell carcinoma is very similar to keratoacanthoma, but is prone to metastasis and has unclear tumour borders. Ultraviolet radiation and the treatment of keratoacanthoma by using chemotherapy are some of the main provocative factors. All three of these diseases are treated surgically. The purpose of this article is to discuss the etiopathogenesis, clinic, diagnosis, treatment of keratoacanthoma, essential complications – skin horn, squamous cell carcinoma, and a clinical case related to these diseases.